Quality-aware sensor data collection. (10th May 2010) - Han, Qi; Hakkarinen, Doug; Boonma, Pruet; Suzuki, Junichi
Many sensor applications often require collecting raw sensed values from many sensor nodes to one centralised server. Sensor data collection typically comes with various quality requirements, e.g. the level of precision requested for temperature values, the time constraints for getting the data, or the percentage of data that is needed. This paper presents a quality-aware sensing framework where characterisations of sensor applications' quality needs are identified and different sensor data collection problems are classified. Two problems and their solutions are then presented as examples to demonstrate how single (or multiple) quality need(s) are satisfied. The paper concludes with suggestions for future research directions that have the potential to complete the framework and provide a holistic approach to sensor applications with diverse quality requirements.